2017
DOI: 10.4253/wjge.v9.i9.428
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy: Current concepts

Abstract: Since early 1990’s, when it was inaugurally introduced, laparoscopic splenectomy has been performed with excellent results in terms of intraoperative and postoperative complications. Nowadays laparoscopic splenectomy is the approach of choice for both benign and malignant diseases of the spleen. However some contraindications still apply. The evolution of the technology has allowed though, cases which were considered to be absolute contraindications for performing a minimal invasive procedure to be treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 78 publications
2
26
0
10
Order By: Relevance
“…There are some risk factors for conversion to open surgery including intraoperative hemorrhage, massive splenomegaly (over 1 kg), a low platelet count, obesity, and adhesions. In the literature, conversion to open rates ranges from 0.7% to 30% (6,(12)(13)(14)(15)(16)(17). In the present study, conversion to open surgery rate was 14.2%, which is comparable with the literature (1,3,6,(12)(13)(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There are some risk factors for conversion to open surgery including intraoperative hemorrhage, massive splenomegaly (over 1 kg), a low platelet count, obesity, and adhesions. In the literature, conversion to open rates ranges from 0.7% to 30% (6,(12)(13)(14)(15)(16)(17). In the present study, conversion to open surgery rate was 14.2%, which is comparable with the literature (1,3,6,(12)(13)(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 88%
“…RLS, which is associated with good exposure, less bleeding, postoperative abdominal pain, shorter length of hospital stay and better cosmetic results, require expertise such as insertion of trocars and ports, proper dissection of hilar vessels, removing of the spleen due to uncontrolled intraoperative hemorrhage and conversion to open splenectomy (11)(12)(13)(14). Many published studies have assessed the safety and practicability of RLS (12)(13)(14)(15)(16)(17). Nevertheless, a few trials are reported regarding the risks factors of conversion to open splenectomy for RLS in the literature (18).…”
Section: Introductionmentioning
confidence: 99%
“…Several patients had complete responses documented in their charts without quantified platelet and hematocrit numbers recorded in our electronic medical record. Splenectomy is generally a safe procedure when performed for hematologic disorders, 9,10 and there were no documented postoperative complications in our limited cohort of patients with Evans syndrome. However, the potential for surgical morbidity, including bleeding and arterial or venous thrombosis, must be taken into account when considering treatment options for patients with autoimmune cytopenias.…”
mentioning
confidence: 67%
“…Some authors advocate complete splenectomy, reducing the possibility of recurrent disease and reducing postoperative bleeding, but most authors recommend a laparoscopic approach, especially for superficial, easily accessible cysts [14,15]. The justification for this attitude stems from the fact that the laparoscopic approach, compared to open surgery, is a minimally invasive procedure providing quick recovery while being safe and effective [16][17][18]. A statistically significant difference, in terms of postoperative complications and recurrence of the disease, has been evidenced by comparing the results of total splenectomy and organ-sparing surgical procedures.…”
Section: Discussionmentioning
confidence: 99%